Effects of Polyphenol Supplementations on Improving Depression, Anxiety, and Quality of Life in Patients With Depression - Lin, Kelly; Li, Yanni; Toit, Eugene Du; Wendt, Lauren; Sun, Jing (Frontiers in Psychiatry, 2021)
Background: Increased prevalence of mental disorders has become a significant public health concern. Recent studies have linked nutrition to depression and anxiety, suggesting that dietary changes or nutritional supplementation may be beneficial in improving mental disorders. Polyphenols have anti-inflammatory and antioxidant properties that may counteract physiological changes in depression and anxiety. This study examined the effectiveness of polyphenol supplementation in improving depression, anxiety and quality of life (QoL). Methods: Randomised controlled trials in English and with polyphenol supplementation as the intervention were searched. The primary outcome was depression, and secondary outcomes were anxiety and QoL. Only studies of at least moderate quality based on the Physiotherapy Evidence Database tool were included. Comprehensive systematic review and meta-analysis were then used to determine the effect of polyphenol supplementations on improving depression, anxiety and quality of life (QoL) in patients with depression. Results: Nineteen studies with 1523 participants were included; 18 studies (n = 1523) were included in the depression meta-analysis, and 5 (n = 188) and 6 (n = 391) in the QoL and anxiety meta-analyses, respectively. Twelve of the 18 studies found significant improvements in depression with polyphenol use, while the meta-analyses results also indicated that polyphenol supplementation significantly improved depression score as compared to control conditions (MD: -2.280, 95% CI: -1.759, -0.133, I2 = 99.465). Although subgroup analyses were conducted a significantly high heterogeneity was still found amongst subgroups. Only 2 of the 5 studies found significant improvements in QoL following polyphenol supplementation and meta-analyses found that polyphenol use did not benefit QoL (MD: -1.344, p < 0.05, I2 = 55.763). For anxiety, 5 of the 6 studies found significant reductions in depression score following polyphenol use but meta-analyses found no significant differences in anxiety score (MD: -0.705, CI: -1.897, 0.487, I2 = 84.06) between polyphenol supplementation and control. Conclusion: The results suggest that polyphenol supplementation is effective in improving depression. Physical illness may act as a risk factor that worsens depression, suggesting the need for preventative supplementation to improve depression. Polyphenol types may have varying effects, which suggests that different populations with depression may benefit from different polyphenols.